RISING TREND OF USING LAPAROSCOPY IN THE TREATMENT OF COMPLICATED APPENDICITIS IN OUR INSTITUTION DURING JANUARY 2017-MAY 2019 - Andrej Nikolovski; Gjorgji Stavridis; Igor Fildishevski; Irina Pavlovska; Svetozar Antovic; Biljana Cvetanovska Ilievski; Angelina Krsteva; Darko Dimitrovski; Burim Elezi; Valjon Saliu; Senol Tahir; Stefan Arsenkov; et al. (Македонско лекарско друштво = Macedonian Medical Association, 2019)
Abstract Introduction. Laparoscopic appendectomy was performed for the first time in the University Clinic for Surgery “St. Naum Ohridski” back in 2003 by the pediatric surgeons. At the moment it is still unrecognized by many senior surgeons as a reliable and safe alternative procedure for acute appendicitis. The end-point of this study is to present the rising trend of using laparoscopy in the treatment of complicated appendicitis. Methods. In the period between January 2017 and May 2019 a total number of 403 patients were operated on due to a preoperative diagnosis of acute appendicitis (270 with open and 133 with laparoscopic appendectomy) and were retrospectively analyzed. Results. Simple appendicitis was diagnosed intraoperatively in 248 patients and complicated appendicitis was diagnosed in 141 patients. The rising trend for overall use of laparoscopy for acute appendicitis was seen during the study period (20.9%, 32.2% and 63.3% in 2017, 2018 and 2019, respectively). In terms of complicated appendicitis, a drastic positive trend followed in favor of laparoscopy (8.9%, 24.6% and 36.7% in 2017, 2018 and 2019, respectively). The negative appendectomy rate with other intraoperative finding was 3.46% (14 cases). The conversion rate was 2.25%. Conclusion. We can finally conclude that the laparoscopic appendectomy is recognized as an effective and safe alternative in the treatment of complicated appendicitis in our institution.
НАГОРЕН ТРЕНД НА УПОТРЕБАТА НА ЛАПАРОСКОПИЈАТА ВО ТРЕТМАНОТ НА КОМПЛИЦИРАН АПЕНДИЦИТИС ВО НАШАТА УСТАНОВА ЗА ПЕРИОД ЈАНУАРИ 2017-МАЈ 2019
Keywords: acute appendicitis; complicated appendicitis; open appendectomy; laparoscopic appendectomy